A Cultural History of India
This book, edited by the well-known historian A. L. Basham, presents a comprehensive survey of Indian culture, covering such aspects as religion, philosophy, social organization, literature, art. architecture, music and science. It includes a special section dealing with the influence of Indian civilization on the rest of the world, as well as details of the political history of the region toprovide a chronological framework for the non-specialist. Contributors include such eminent scholars as Professor S. Radhakrishnan, Professor T. Burrow, Professor S. N. Das and Dr Percival Spear.